Nortel Networks : how innovation and vision created a network giant - MacDonald, Larry (New York : John Wiley and Sons, 2000)
This book presents A Brief History of Nortel networks; and Key Executives in the History of Nortel Networks. xc.
Keywords: Nortel Networks; Telecommunications; Canada; Nortel Networks (Firm) -- History; Telecommunications -- Canada -- History